Partisipasi Masyarakat dalam Program Klaster Berdaya di PKPU Pekanbaru - Moralely Hendrayani (IAIN Salatiga, 2019)
This study aimed to see how community participation in the empowerment program in PKPU Pekanbaru with a qualitative approach research method, the results obtained were that community participation in identifying community problems was involved and the community attended and PKPU also informed the community about the program and the purpose of activities for the community in advance. In the planning and implementation of the community following the activities but not all people were present, in the evaluation activities, monitoring the community supervised together with the supervision that also helped oversee the business being carried out, and in measuring the negative impact, the community felt directly the changes before and after the existence of Powerful Cluster Program